Parathyroid hormone exerts disparate effects on osteoblast differentiation depending on exposure time in rat osteoblastic cells. - Ishizuya, T (1997)
It has been reported that PTH exerts bone-forming effects in vivo when administered intermittently. In the present study, the anabolic effects of PTH(1-34) on osteoblast differentiation were examined in vitro. Osteoblastic cells isolated from newborn rat calvaria were cyclically treated with PTH(1-34) for the first few hours of each 48-h incubation cycle. When osteoblastic cells were intermittently exposed to PTH only for the first hour of each 48-h incubation cycle and cultured for the remainder of the cycle without the hormone, osteoblast differentiation was inhibited by suppressing alkaline phosphatase activity, bone nodule formation, and mRNA expression of alkaline phosphatase, osteocalcin, and PTH/PTHrP receptor. Experiments using inhibitors and stimulators of cAMP/protein kinase A (PKA) and Ca2+/PKC demonstrated that cAMP/PKA was the major signal transduction system in the inhibitory action of PTH. In contrast, the intermittent exposure to PTH for the first 6 h of each 48-h cycle stimulated osteoblast differentiation. Both cAMP/ PKA and Ca2+/PKC systems appeared to be involved cooperatively in this anabolic effect. Continuous exposure to PTH during the 48-h incubation cycle strongly inhibited osteoblast differentiation. Although both cAMP/PKA and Ca2+/PKC were involved in the effect of continuous exposure to PTH, they appeared to act independently. A neutralizing antibody against IGF-I blocked the stimulatory effect on alkaline phosphatase activity and the expression of osteocalcin mRNA induced by the 6-h intermittent exposure. The inhibitory effect induced by the 1-h intermittent exposure was not affected by anti-IGF-I antibody. These results suggest that PTH has diverse effects on osteoblast differentiation depending on the exposure time in vitro mediated through different signal transduction systems. These in vitro findings explain at least in part the in vivo action of PTH that varies with the mode of administration.